Risk factors associated with multidrug-resistant tuberculosis in Espírito Santo, Brazil - Geisa Fregona; Lorrayne Belique Cosme; Cláudia Maria Marques Moreira; José Luis Bussular; Valdério do Valle Dettoni; Margareth Pretti Dalcolmo; Eliana Zandonade; Ethel Leonor Noia Maciel (Revista de Saúde Pública)
ABSTRACT OBJECTIVE To analyze the prevalence and factors associated with multidrug-resistant tuberculosis in Espírito Santo, Brazil. METHODS This is a cross-sectional study of cases of tuberculosis tested for first-line drugs (isoniazid, rifampicin, pyrazinamide, ethambutol, and streptomycin) in Espírito Santo between 2002 and 2012. We have used laboratory data and registration of cases of tuberculosis – from the Sistema Nacional de Agravos de Notificação and Sistema para Tratamentos Especiais de Tuberculose. Individuals have been classified as resistant and non-resistant and compared in relation to the sociodemographic, clinical, and epidemiological variables. Some variables have been included in a logistic regression model to establish the factors associated with resistance. RESULTS In the study period, 1,669 individuals underwent anti-tuberculosis drug susceptibility testing. Of these individuals, 10.6% showed resistance to any anti-tuberculosis drug. The rate of multidrug resistance observed, that is, to rifampicin and isoniazid, has been 5%. After multiple analysis, we have identified as independent factors associated with resistant tuberculosis: history of previous treatment of tuberculosis [recurrence (OR = 7.72; 95%CI 4.24–14.05) and re-entry after abandonment (OR = 3.91; 95%CI 1.81–8.43)], smoking (OR = 3.93; 95%CI 1.98–7.79), and positive culture for Mycobacterium tuberculosis at the time of notification of the case (OR = 3.22; 95%CI 1.15–8.99). CONCLUSIONS The partnership between tuberculosis control programs and health teams working in the network of Primary Health Care needs to be strengthened. This would allow the identification and monitoring of individuals with a history of previous treatment of tuberculosis and smoking. Moreover, the expansion of the offer of the culture of tuberculosis and anti-tuberculosis drug susceptibility testing would provide greater diagnostic capacity for the resistant types in Espírito Santo.